2014
DOI: 10.1016/j.jspd.2014.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analyses of Patients With Unexplained Early-Onset Scoliosis

Abstract: Study Design To test for rare genetic mutations, a cohort of patients with unexplained early onset scoliosis (EOS) was screened using high-density microarray genotyping. A cohort of patients with adolescent idiopathic scoliosis (AIS) was similarly screened, and the results were compared. Summary of background data Patients with scoliosis in infancy or early childhood (EOS) are at high risk for progressive deformity and associated problems including respiratory compromise. EOS is frequently associated with ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…Studies were admitted to this paper's analysis when the following criteria were met: (1) the study detailed parent of origin data for one of the 38 eligible NAHR-mediated loci as designated by Coe et al [7], (2) the authors of the study interrogated the entire canonical CNV interval to confirm the presence of a deletion or duplication in the patients, (3) the authors determined the investigated CNVs were de novo, and (4) the study clearly treated monozygotic twins as one meiotic event and not two (Additional file 1: Supplemental Methods, Additional file 2: Table S1, and Additional file 3: Table S2). The literature search led to a manual review of 1268 papers, out of which we identified 77 manuscripts across 24 loci with suitable data for analysis: 1q21.1 [35][36][37][38][39], 1q21.1 TAR [40], 2q13 [37], 3q29 [37][38][39][40][41][42], 5q35 [31,32], 7q11.23 [24,40,[43][44][45][46][47][48][49][50][51][52][53][54], 8p23.1 [55,56], 11q13.2q13.4 [57], 15q13.3 [38,40,58], 15q24 (AC, AD, BD, and BE intervals) [59][60]…”
Section: Literature Search and Parental Origin Data Curationmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were admitted to this paper's analysis when the following criteria were met: (1) the study detailed parent of origin data for one of the 38 eligible NAHR-mediated loci as designated by Coe et al [7], (2) the authors of the study interrogated the entire canonical CNV interval to confirm the presence of a deletion or duplication in the patients, (3) the authors determined the investigated CNVs were de novo, and (4) the study clearly treated monozygotic twins as one meiotic event and not two (Additional file 1: Supplemental Methods, Additional file 2: Table S1, and Additional file 3: Table S2). The literature search led to a manual review of 1268 papers, out of which we identified 77 manuscripts across 24 loci with suitable data for analysis: 1q21.1 [35][36][37][38][39], 1q21.1 TAR [40], 2q13 [37], 3q29 [37][38][39][40][41][42], 5q35 [31,32], 7q11.23 [24,40,[43][44][45][46][47][48][49][50][51][52][53][54], 8p23.1 [55,56], 11q13.2q13.4 [57], 15q13.3 [38,40,58], 15q24 (AC, AD, BD, and BE intervals) [59][60]…”
Section: Literature Search and Parental Origin Data Curationmentioning
confidence: 99%
“…Data are consolidated by locus. BED coordinates correspond to hg38 (LiftOver from hg18 coordinates in Coe et al[7])intervals)[59][60][61][62][63][64], 15q25.2[65][66][67],16p11.2[26,37,40,[68][69][70], distal 16p11.2[37,38,70], 16p11.2p12.1[71], 16p31.11[37], 17p11.2[72][73][74][75][76], 17q11.2[28,29,77], 17q12[37,38,78], 17q21.31[19,25,67,[79][80][81][82][83][84], 17q23.1q23.2[69,85] and 22q11.2[30,43,53,[86][87][88][89]…”
mentioning
confidence: 99%
“…The 16p11.2 microdeletion was found to be associated with CS [13], and recent studies demonstrated that a compound inheritance of a TBX6-containing 16p11.2 microdeletion and a TBX6 mutation or hypomorphic haplotype accounted for 5-10% of patients with CS in different populations [14][15][16][17]. Additional CNVs, including 10q24.31, 17p11.2, 20p11, 22q11.2, and a few other regions, were respectively reported in individual patients with CVMs [18,19]. Besides 16p11.2 microdeletion, it is unknown whether other CNVs are prevalent in CS.…”
Section: Introductionmentioning
confidence: 98%
“…in 2007, with many more cases now reported and the prevalence assessed to be 3:10,000-4:10,000 ([Klopocki et al, 2008;Marshall et al, 2008;Kiholm Lund, et al, 2008;Andrieux et al, 2009;El-hattab et al, 2009;Masurel-Paulet et al, 2009, Van Esch et al, 2009El-Hattab et al, 2010;McInnes et al, 2010;Ng et al, 2011;Brun et al, 2012;Mefford et al, 2012aMefford et al, , 2012bNarumi et al, 2012;Gao et al, 2014;Samuelsson et al, 2015;Siu etal.,2016;Palazon-Bru et al, 2016;Romano et al, 2017;Ahram et al, 2017;Huynh et al,2017;Dai et al, 2017;Wang et al, 2019]). Most of 15q24 deletions were found between 1.7 and 6.1 Mb in size with breakpoints localized to the clusters of five low copy regions (LCRs) from centromere to telomere, which were identified and designated as LCR15q24A (BP4), B High anterior hairline 5 (11.1) 4 (8.9) 3 (6.7) 1 (2.2)…”
mentioning
confidence: 99%